An Analytical Assessment of Mathematical Learning of Students of North-East Delhi - Teotia, Anil Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Students, bypassing over different grades, show a fall in the mathematical achievement level. In the following paper, we tried to analyse the learning level of the students of the North-East district of Delhi. NCERT developed Learning Outcomes for each grade from I to VIII classes regarding these learning outcomes. We found that the learning of mathematics is not at all satisfactory in the schools. Students show the inferior quality of mathematical understanding; we tried to find out the poorly developed concepts and the reasons behind this. We also tried to find out the highest developed concept of mathematics in students and the ideas for it. Lack of pedagogical understanding in teachers, no use of concrete material, non-revisiting of the previous concepts are some of the reasons behind low performance of the students, on the other hand, visual ideas of mathematics, and thoughts that develop automatically with no or little help of school developed better in the minds of kids. We find that a majority of teachers say that they have full understating of curricular expectations and know the entire pedagogy, but the result which was obtained about students’ learning level speaks different picture. The majority of kids say that it is challenging for them to understand teachers’ talk in the classroom, but almost all the students like to come to school whatsoever is the reason.